PEMBELAJARAN TEKNIK DASAR PEMERANAN OLAH SUARA DALAM SENI TEATER MENGGUNAKAN STRATEGI PROJECT BASED LEARNING PADA SISWA KELAS IX DI SMP NEGERI 1 BIAU - Endah, Endah Nur Fauziyyah; Semiaji, Trubus; Pulukadang, Mimy A.; Karlan, La Ode; Sitharesmi, Riana Diah (SINERGI : Jurnal Riset Ilmiah, 2025)
This study aims to explore the process of teaching voice acting techniques in theater art through the Project-Based Learning strategy for Class IX students at SMP Negeri 1 Biau.The study employed a qualitative approach with a descriptive method. Data collection techniques include observation,interview,and documentation. The findings indicate that implementing the “Teaching Basic Voice Acting Techniques in Theater Art Using Project-Based Learning Strategy for Class IX Students at SMP Negeri 1 Biau”was successful,achieving a success rate of 83.3%. The researcher concluded that the study was successful based on two considerations: first,both student groups could perform the theater scripts,although one group was less optimal;second,several students achieved good or Dere-than-satisfactory results,with satisfactory performance scores.Using the ffroiceeBased Learning strategy proved effective in the implementation of teaghoge mie,ciieluding the design and execution of performances.